REMEDIASI MISKONSEPSI PESERTA DIDIK TENTANG GETARAN MENGGUNAKAN MODEL PEMBELAJARAN PDEODE BERBANTUAN LABINAPP DI SMP - Ratia Indriyani; Stepanus Sahala Sitompul; Syukran Mursyid (Universitas Tanjungpura, 2021)
AbstractThis study aims to asses the effectiveness of PDEODE Learning Model with LabInApp to remediate student’s misconception about ‘vibration’ for grade VIII IPA student of MTs Al-Madani Pontianak. The method used in This research method was pre-experimental with the one-group pretest-posttest design. Samples of study were purposive sampling and selected base on Physivcs teacher’s recommendation. The instrument of research included 10 questions of diagnostic test. The average range of students misconception in pre test was 73,1% and in post test was 26,9% . The average range decreases 57,9% after the treatment. Based on McNemar test, overall students experienced significant misconception with value of χ2count (54,39) > χ2table (3,84), df=1 and α = 5%. The effectiveness of PDEODE Model with LabInApp to remediate student’s misconception about ‘vibration’ that used to reduce the misconcepted students through DQM of 55,64% which included in medium category. Therefore, teachers suggested to used guided inquiry learning model as alternative learning technique in order to straighten out student misconception about ‘vibration’.Keywords: Remediation, PDEODE, LabInApp.